ANALISIS KINERJA KEUANGAN TERHADAP KINERJA SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA BADAN USAHA MILIK NEGERA (BUMN) DI BURSA EFEK INDONESIA - Agung Anggoro Seto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The study aims to find out the impact of financial performance with liquidity variables, solvency, and activity on stock performance with profitability as an intervening variable on SOEs post-privatization on the Indonesia Stock Exchange. The population in this research is the entire IDX-listed SOEs. Sampling techniques use purposive sampling with a total of 5 SOEs. This type of research is associated with analytical techniques using path analysis. The results found that there was a significant negative influence between the liquidity ratio and the solvency to partial profitability with the P-value each of-0.021 and-0.000. While the ratio of activity affects significant positive to profitability with a P-value value of 0.000. The research also found that liquidity and solvency also have a significant negative impact on stock performance with the price earning ratio indicator with P-value respectively – 0.039 and-0.006. The ratio of activity and profitability positively affects the stock performance with P-value each of 0.000 and 0.013. The results of this study also proved that the profitability variables proved to be the ability of the liquidity ratio, solvency, and activity to the stock performance of state-owned enterprises in the Indonesia Stock Exchange after privatization